An identification guide to the genera of aquatic larval Chironomidae (Diptera) of south-east Asia - Cranston, Peter S.; Tang, Hongqu (Zootaxa, 2024)
We provide illustrated dichotomous keys for the identification of final (4th) instar larvae of south-east Asian genera of Chironomidae (Diptera), predominantly from aquatic (freshwater and maritime) habitats. The region considered comprises oriental China, Burma, Thailand, Malaysia (west and east), Brunei, Singapore and Indonesia. Eight subfamilies are represented and phylogenetically validated tribes are keyed. Terminal taxa, listed in the sequence used in this guide, comprise 28 genera of Tanypodinae, 71 of Chironominae, 2 of Podonominae, 1 of Buchonomyiinae, 8 of Diamesinae, 2 of Protanypodinae, 5 of Prodiamesinae, 2 of Telmatogetoninae and 61 of Orthocladiinae. The morphology terminology is standard for larval Chironomidae to which users are referred. Illustrations of selected features are provided as photographs with important details labelled. Short summaries of ecology and concise details of selected species and regional / global distribution are provided in brackets under each entry. Some suspect new synonymy is alluded to, but will be addressed formally in more detail elsewhere.